Effect of indirect and direct teacher influence on dependent-prone students learning outcomes in geometry (2006)
Personality factors and teachers' teaching style are among the many factors that affect students' learning. In the study, the writer examine the effect of direct and indirect teacher influence on dependence-prone students' learning outcomes in geometry at the senior secondary school level. The top 25% (216) based on the scores of 864 on a dependence-prone test were used in the study. The 216 identified dependence-prone students were divided into two groups and each was exposed to the two constracting teacher-talk strategies (direct verus indirect). Using both descriptive and multivariate statistical analysis, results showed that treatment contributed significantly to the variations in the dependent-prone students' mean cognitive achievement in geometry. A major implication of this study is that closer supervision through the use of direct influence, an all common antidote to lower achievement in mathematics and the sciences, may be harmful to dependent-prone students